Empirically derived dietary patterns and obesity among Iranian Adults: Yazd Health Study‐TAMYZ and Shahedieh cohort study - Sahar Sarkhosh‐Khorasani (Food Science & Nutrition, 2020)
Abstract The aim was to determine the relationship between dietary patterns derived by principal component analysis (PCA) in association with obesity from a large group of Iranian adults in the urban and suburb areas. A cross‐sectional study was conducted on 10,693 Iranian adults. The data were collected from two cohort studies: Shahedieh city annexed to Yazd area as well as Yazd Health Study (YaHS)‐TAMYZ (Yazd Nutrition Survey in Persian) in urban area. Dietary intakes were assessed using a validated semi‐quantitative food frequency questionnaire. The PCA was applied to identify the dietary patterns. Multiple logistic regressions were run to assess the relationship between dietary patterns and obesity. In Shahedieh cohort study, three major dietary patterns were identified traditional, unhealthy, and prudent pattern. Prudent pattern was associated with lower odds of obesity (OR: 0.68; 95% CI: 0.53, 0.88). Higher adherence to the unhealthy (OR: 1.24; 95% CI: 1.02, 1.50) and traditional (OR: 1.38; 95% CI: 1.11, 1.72) patterns was related to greater odds of obesity. Moreover, we identified traditional and unhealthy dietary patterns in YaHS study. Higher adherence to the unhealthy dietary pattern was associated with greater odds of obesity (OR: 1.21 95% CI: 1.02, 1.44). Greater adherence to unhealthy dietary patterns was associated with higher odds of obesity in participants. Greater adherence to traditional and prudent dietary patterns increased and decreased the obesity odds, respectively. Further prospective studies are needed to find out the causal relationship between the variables.